Effect of the combination of C.domestica extract and essential oil of C.xanthorrhiza roxb. on leucocyte count in synovial fluid compared to that of pyroxicam - Kertia, Nyoman; A.D., Imono; ., Mufrod; Catur, Eny; Rahardjo, Poerwono; Asdie, Ahmad Husain (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Osteoarthritis (OA) is the most prevalence rheumatic disease. The non steroidal antiinflamatory drugs display some side effect especially on the gastrointestinal tract, liver, kidney and blood clotting. Kunyit (Curcuma domestica L.) and temulawak (Curcuma xanthorrhiza Roxb.) as natural herbal remedies are developed for antiinflammation, antioxidant and cholagoga. The aim of this present research was to study the effect of combination of Curcuma domestica extract and essential oil of Curcuma xanthorrhiza Roxb on the leucocyte count in the synovial fluid of patient with osteoarthritis compared to that of pyroxicam. A double blind randomized clinical trial was used and conducted at Dr. Sardjito Hospital Yogyakarta. After washed out period the knee synovial fluid was aspirated and the leucocyte count was examined. Patients were randomized for receiving piroxicam capsule 10 mg twice daily or combination of 3,66 ± 0,65 % w/w curcuminoid extract of Curcuma domestica L.and 25 ml essential oil containing curcumen, bergamoten germacren B, Curserenon, Germacron, Xanthorrizol as a major component with 27,64 ± 0,85 % relative concentration of xanthorrhizol each capsule; two times a day for two week period. At the end of this study the synovial fluid was examined. Decreasing the inflamation of synovial area was parrallel with decreasing leucocyte count by 174.56 ± 161.73 per mm3 (p